In situelectromagnetic field diagnostics with an electron plasma in a Penning–Malmberg trap - Michael Charlton (New Journal of Physics, 2014)
We demonstrate a novel detection method for the cyclotron resonance frequency of an electron plasma in a Penning–Malmberg trap. With this technique, the electron plasma is used as an in situ diagnostic tool for the measurement of the static magnetic field and the microwave electric field in the trap. The cyclotron motion of the electron plasma is excited by microwave radiation and the temperature change of the plasma is measured non-destructively by monitoring the plasma’s quadrupole mode frequency. The spatially resolved microwave electric field strength can be inferred from the plasma temperature change and the magnetic field is found through the cyclotron resonance frequency. These measurements were used extensively in the recently reported demonstration of resonant quantum interactions with antihydrogen.